Electrical ventricular remodeling in dilated cardiomyopathy - Mages, Christine; Gampp, Heike; Syren, Pascal; Rahm, Ann-Kathrin; André, Florian; Frey, Norbert; Lugenbiel, Patrick; Thomas, Dierk (Cells, 2021)
Ventricular arrhythmias contribute significantly to morbidity and mortality in patients with heart failure (HF). Pathomechanisms underlying arrhythmogenicity in patients with structural heart disease and impaired cardiac function include myocardial fibrosis and the remodeling of ion channels, affecting electrophysiologic properties of ventricular cardiomyocytes. The dysregulation of ion channel expression has been associated with cardiomyopathy and with the development of arrhythmias. However, the underlying molecular signaling pathways are increasingly recognized. This review summarizes clinical and cellular electrophysiologic characteristics observed in dilated cardiomyopathy (DCM) with ionic and structural alterations at the ventricular level. Furthermore, potential translational strategies and therapeutic options are highlighted.
Gesehen am 06.12.2021